Effects of plateau time on Cervical Vestibular Evoked Myogenic Potential (cVEMP) elicited by 500-Hz tone burst - Vijay Marimuthu; Mohd Fairul Syafiq Harun (Penerbit UKM, 2016)
Cervical Vestibular Evoked Myogenic Potential (cVEMP) is a routine vestibular test which checks the integrity of vestibulocollic reflex (VCR) pathway. Clinically, 500-Hz tone burst is widely used stimulus to evoke a cVEMP. Although several studies have suggested different plateau times (PT) for eliciting cVEMPs, but not many have reported the optimal PT for evoking cVEMP using 500 Hz tone burst stimuli. Therefore, the present study aimed to investigate the effect of PT on cVEMPs elicited by 500 Hz tone burst at 95 dBnHL using four different PT (0, 2, 4 and 10 ms). Thirty healthy adults with normal hearing and vestibular systems participated in this study. Results revealed that the P1 latency was significantly longer for PT 10 ms compared to other PTs. N1 latency was significantly prolonged for long PT of 10 ms compared to PT 2 ms. P2 latency showed no significant differences among PTs. The P1-N1 inter-amplitude values however revealed no significant difference across all PTs. It was found that the P1-N1 inter-amplitude was severely affected after 4 ms of PT. This study concluded that the PT of either 0 or 2 ms yielded the most robust cVEMP.